Reality show, a philosophical question - Vuksanović, Divna (Napredak, 2023)
From the point of view of the philosophy of media, the text tries to point out the importance of analyzing reality shows in the context of philosophical reflections on this topic, primarily in the domain of socio-humanistic research, as well as regarding the current role and position of the media in society, at a global level. In our opinion, the reality show is a typical media product of late capitalism, calculated on profit and entertainment. However, the basic concept and effect of reality shows on the audience depend on the idea of production, and the content of these formats varies from „socially useful” (for capitalism) to morally controversial and highly provocative (violence and pornography). Basically, if it is substantiated, the philosophical criticism of reality shows should point to the ontological dimension, as well as the socioeconomic framework of questioning in which reality shows are present and useful for maintaining the status quo for the ruling class (the so-called elite), to the detriment of the poor and oppressed.
Keywords: reality shows; media; capitalism; criticism; philosophy of media